2018
DOI: 10.12968/jpar.2018.10.7.292
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bad news and managing family during an out-of-hospital cardiac arrest

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In a small study of semistructured interviews with paramedics it was highlighted that clinicians primarily learnt how to break bad news through observing others, leading to a wide variety of skills and styles of breaking bad news and a general feeling of discomfort with the practice. 3 This feeling of discomfort is not unique to the paramedic profession; similar findings have been observed in studies of doctors and medical students. 4 When doctors and medical students get specific training, this helps build their confidence in the act of breaking bad news and assists both the clinician and family member to have better outcomes from the experience.…”
Section: Challenges and Considerations In Out-of-hospital Bad News Desupporting
confidence: 67%
See 1 more Smart Citation
“…In a small study of semistructured interviews with paramedics it was highlighted that clinicians primarily learnt how to break bad news through observing others, leading to a wide variety of skills and styles of breaking bad news and a general feeling of discomfort with the practice. 3 This feeling of discomfort is not unique to the paramedic profession; similar findings have been observed in studies of doctors and medical students. 4 When doctors and medical students get specific training, this helps build their confidence in the act of breaking bad news and assists both the clinician and family member to have better outcomes from the experience.…”
Section: Challenges and Considerations In Out-of-hospital Bad News Desupporting
confidence: 67%
“… 5 6 Some clinicians feel the protection they have from the emotional reality of their work slips in these moments. As one paramedic interviewed in the Mainds and West 3 study said, it ‘ pulls you from back out of the clinical and into the human ’. These are the times when we are no longer just the professional doing our job but are a part of an intensely human and emotionally resonant scenario.…”
Section: Challenges and Considerations In Out-of-hospital Bad News Dementioning
confidence: 99%
“… 55 71 During OHCAs, some PHPs preferred families not to be present in the room during resuscitation and described feeling pressure from families, and expressions of disquiet related to their presence. 69 Others considered that relatives could aid resuscitation by putting on hold their own feelings and emotions, thus helping PHPs focus on the condition of the patient. 76 77 PHPs and families could provide mutual reassurance following unsuccessful resuscitations, that efforts were not inappropriate.…”
Section: Resultsmentioning
confidence: 99%
“…Nine included studies reported inadequate training and/or a desire for more training in this area (27)(28)(29)(30)(32)(33)(34)36,39,41). Results from qualitative research by Bremer, Dahlberg and Sandman (36) Mainds and Jones (32) and Fernández-Aedo et al (33) all found ambulance personnel participants felt particularly concerned about the skills required to deliver death notification and communicate with family and bystanders. Tataris et al's (27) recent survey of over 2000 Chicago Emergency Medical Service providers showed that 36% of respondents had no training in performing death notification, and only 25% had received training through certification courses.…”
Section: Resultsmentioning
confidence: 99%
“…• Termination of resuscitation guideline derivation, prognostic indicators and survival statistics (30,42) • Local medicolegal issues including documented patient wishes (28,31) Improved self-confidence through rehearsal/role-play and discussion of: • Managing death scenes and bystanders (27)(28)(29)(30)(32)(33)(34)36,39,41) • Death notification delivery and communication with bereaved family (27)(28)(29)(30)33,36,38,39) Identified support needs Access to: • Clear policies or guidelines (36,41) • Informal peer support and opportunities to discuss difficult decisions (33,35,36) • Professional support for occupational or personal stressors (30,42)…”
Section: Identified Preparation Needsmentioning
confidence: 99%